Standortbewertung mit Fuzzy Logic: Ein neuer Weg der EDV-Unterstützung im kommunalen Standortmarketing - Wolfertz, Klaus (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
In today’s competitive environment, local authorities are forced to adopt a strategic approach to locational marketing. However, all too often they do not have the resources required to develop a strategy which is thoroughly researched. In such cases marketing measures will almost inevitably fail to meet expectations. A possible remedy is provided by what is referred to as a „knowledge-based system”, which supports economic-development agencies at localauthority level in the search for the right strategy. In processing the information required, which tends in most cases to be either incomplete or „fuzzy”, a key role is played by methods associated with fuzzy logic. Preliminary tests in practice using a system programmed in this way are very promising.